System performances analysis of reservoir optimizationsimulation model in application of artificial bee colony algorithm - Hossain M.S.; El-Shafie A.; Mahzabin M.S.; Zawawi M.H. (Springer London, 2023)
Decision making; Evolutionary algorithms; Genetic algorithms; Optimization; Particle swarm optimization (PSO); Reservoirs (water); Stochastic models; Stochastic systems; Artificial bee colonies (ABC); Artificial bee colony algorithms; Optimization techniques; Performance checking indices; Performances analysis; Reservoir optimizations; Reservoir release; Stochastic dynamic programming; Dynamic programming